Chondrodysplasias With Multiple Dislocations Caused by Defects in Glycosaminoglycan Synthesis - Dubail, Johanne; Cormier-Daire, Valérie (Frontiers in Genetics, 2021)
Chondrodysplasias with multiple dislocations form a group of severe disorders characterized by joint laxity and multiple dislocations, severe short stature of pre- and post-natal onset, hand anomalies, and/or vertebral anomalies. The majority of chondrodysplasias with multiple dislocations have been associated with mutations in genes encoding glycosyltransferases, sulfotransferases, and transporters implicated in the synthesis or sulfation of glycosaminoglycans, long and unbranched polysaccharides composed of repeated disaccharide bond to protein core of proteoglycan. Glycosaminoglycan biosynthesis is a tightly regulated process that occurs mainly in the Golgi and that requires the coordinated action of numerous enzymes and transporters as well as an adequate Golgi environment. Any disturbances of this chain of reactions will lead to the incapacity of a cell to construct correct glycanic chains. This review focuses on genetic and glycobiological studies of chondrodysplasias with multiple dislocations associated with glycosaminoglycan biosynthesis defects and related animal models. Strong comprehension of the molecular mechanisms leading to those disorders, mostly through extensive phenotypic analyses of in vitro and/or in vivo models, is essential for the development of novel biomarkers for clinical screenings and innovative therapeutics for these diseases.